APPLICATION OF TRIPLE EXPONENTIAL SMOOTHING METHOD FOR PREDICTING THE PRICE MOVEMENT OF CRYPTOCURRENCY ETHEREUM - Maurizio Zanardi; Hizamrul Jaen (PT. Radja Intercontinental Publishing, 2023)
An innovation that was sparked is an alternative currency to replace conventional currency, namely digital currency that is secured using a Cryptographic method called Cryptocurrency. However, Cryptocurrency prices cannot be controlled, causing massive fluctuations. Cryptocurrency price changes are very stable due to several factors such as speculation from users and the nature of the follow-up from new to one of the causes. The cause of this bandwagon is due to extreme price increases in a short time, even within a day the price of Crypto can experience a difference of millions of rupiah for each increase and decrease. To answer this question, we need a software that can predict the Rupiah exchange rate. The Mean Absolute Percentage Error (MAPE) for the Triple Exponential Smoothing implementation is 3.7249%. This method was utilized to predict the Rupiah exchange rate for Cryptocurrency, addressing the issue of price fluctuations in the Crypto market. Historical data, along with the specified parameters of 0.40 for Xt and S't, and 0.60 for Beta, were employed to generate accurate predictions. The process involved calculating first to third smoothing, determining Constants, Slopes, and Parabolics, and finally producing the Forecasting results. The MAPE value of 3.7249% indicates that the Triple Exponential Smoothing method exhibited relatively accurate predictions with a small margin of error when applied to a dataset of 50 data samples, ranging from May 2022 to June 2022.